Dynamical conditions of ice supersaturation and ice nucleation in convective systems: A comparative analysis between in situ aircraft observations and WRF simulations. Issue 5 (3rd March 2017) - D'Alessandro, John J.; Diao, Minghui; Wu, Chenglai; Liu, Xiaohong; Chen, Ming; Morrison, Hugh; Eidhammer, Trude; Jensen, Jorgen B.; Bansemer, Aaron; Zondlo, Mark A.; DiGangi, Josh P.
Abstract: Occurrence frequency and dynamical conditions of ice supersaturation (ISS, where relative humidity with respect to ice (RHi) > 100%) are examined in the upper troposphere around convective activity. Comparisons are conducted between in situ airborne observations and the Weather Research and Forecasting model simulations using four double‐moment microphysical schemes at temperatures ≤ −40°C. All four schemes capture both clear‐sky and in‐cloud ISS conditions. However, the clear‐sky (in‐cloud) ISS conditions are completely (significantly) limited to the RHi thresholds of the Cooper parameterization. In all of the simulations, ISS occurrence frequencies are higher by 3–4 orders of magnitude at higher updraft speeds (>1 m s −1 ) than those at the lower updraft speeds when ice water content (IWC) > 0.01 g m −3, while observations show smaller differences up to 1–2 orders of magnitude. The simulated ISS also occurs less frequently at weaker updrafts and downdrafts than observed. These results indicate that the simulations have a greater dependence on stronger updrafts to maintain/generate ISS at higher IWC. At lower IWC (≤0.01 g m −3 ), simulations unexpectedly show lower ISS frequencies at stronger updrafts. Overall, the Thompson aerosol‐aware scheme has the closest magnitudes and frequencies of ISS >20% to the observations, and the modified Morrison has the closest correlations between ISS frequencies and vertical velocity at higher IWC and number density. The Cooper parameterization often generates excessive ice crystals and therefore suppresses the frequency and magnitude of ISS, indicating that it should be initiated at higher ISS (e.g., ≥25%). Key Points: Ice supersaturation (ISS) occurrence frequencies in simulations show greater dependence on vertical velocity than observations Cooper parameterization of ice crystal formation suppresses ISS magnitude and frequency Model‐observation comparison results show improvements by limiting ice nucleation at lower ISS